Prince Frog Face - Umansky, Kaye (Edinburgh: Barrington Stoke, 2015)
Prince Valentine of Romantica is absolutely outraged - some raggedy old witch has had the audacity to turn him into a frog! A FROG! This just cannot be allowed to stand. He's far too busy interviewing princesses for the honoured post of his girlfriend to be hopping around and squatting in murky water. He had a points system and everything. But apparently he needs to learn manners. Honestly, some people ... A side-splitting comedy caper, complete with Kaye Umansky's sparkling wit and spot-on humour, this is sure to be a hit with boys and girls of all ages. Particularly suitable for struggling, reluctant and dyslexic readers aged 8+
Keywords: Children's stories